Amoxicillin, the Main Drug for Treating Community-Acquired Pneumonia and Otitis Media, Recommended but Often Not Followed - M. D. Bakradze; V. K. Tatochenko; A. S. Polyakova; I. L. Chashchina; T. A. Khokhlova; D. D. Gadliya; O. A. Rogova (Педиатрическая фармакология)
Background: Amoxicillin is the drug of choice for treating the majority of community-acquired respiratory tract infections in children, including pneumonia and acute otitis media according to both international and national guidelines. Nevertheless, the practice of not following these guidelines is widespread.Objective: Our aim was to study a range of antibiotics prescribed prior to hospitalization to children with community-acquired pneumonia (CAP) and acute otitis media (AOM), and to evaluate their effectiveness.Methods. Observational study of children with hospital-verified diagnosis CAP or AOM.Results. Amoxicillin was prescribed to only 4.5% of children with CAP and 1% of patients with AOM; along with parenteral cephalosporines and amoxicillin/clavulanate in adequate doses therapy was started in 34 and 25% respectively. Other children received 3d generation oral cephalosporines or macrolides, which rendered a very low effectiveness (19 and 10% respectively). In view of a flagrant inconformity of the prescribed antibiotics and their doses to the guidelines, non-effective prescriptions were made for 72% of children with CAP and 69% — with AOM. For children with atypical pneumonia macrolides were prescribed in only 19%.Conclusion. Since amoxicillin remains the main drug for treating infections caused by an ever increasing number of resistant strains of S. pneumonia and S. pyogenes, it should be prescribed to children with CAP and AOM: its doses (as well as doses of amoxicillin/clavulanate) should be not less than 45 mg/kg/d, and in risk group patients — 80–100 mg/kg/d. The pediatricians’ skills of differentiating atypical pneumonia should be improved.